2001
DOI: 10.2224/sbp.2001.29.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Impressions Based on Frequency of Blinking

Abstract: The purpose of this study was to investigate the influence of frequency of blinking on creating a personal impression. The subjects were 88 Japanese university students, 35 males and 53 females, who rated stimulus persons on a seven-point semantic differential scale. The stimulus persons, two males and two females, were presented on a 20-second video simulating various blink rates, i.e., 3, 6, 9, 12, 18, 24, 36, 48, 72, and 96 blinks/min. A factor analysis of the ratings yielded three factors, interpreted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Blinking behaviour affects the impression that an actor makes on the observer; moderately‐blinking human‐like avatars are rated friendly, frequently‐blinking ones are rated nervous, and infrequently‐blinking ones are rated intelligent (Takashima et al ., ). Similar tendencies are true for humans; people who blink very often are perceived as nervous, unfriendly, or careless (Omori & Miyata, ). Interestingly, it has been claimed that Walter Mondale was rated less favourably than Roland Reagan during the TV debates of the 1984 presidential elections, because Mondale blinked very frequently (more than once per second), and made less gaze and head movements than Reagan (Patterson et al ., ).…”
Section: Introductionmentioning
confidence: 72%
“…Blinking behaviour affects the impression that an actor makes on the observer; moderately‐blinking human‐like avatars are rated friendly, frequently‐blinking ones are rated nervous, and infrequently‐blinking ones are rated intelligent (Takashima et al ., ). Similar tendencies are true for humans; people who blink very often are perceived as nervous, unfriendly, or careless (Omori & Miyata, ). Interestingly, it has been claimed that Walter Mondale was rated less favourably than Roland Reagan during the TV debates of the 1984 presidential elections, because Mondale blinked very frequently (more than once per second), and made less gaze and head movements than Reagan (Patterson et al ., ).…”
Section: Introductionmentioning
confidence: 72%
“…Eye-blink behavior may have developed as a means of remote visual communication. The observation that the blink rate affects the formation of a person's impression in humans is a suggestive example of eye-blinking as a social communication tool [66]. This hypothesis may also be indirectly supported by the “colorful” primates [67].…”
Section: Discussionmentioning
confidence: 99%
“…Results from behavioral studies support the idea that observed blinks are not ignored. Very frequent blinkers are more likely to be rated as nervous or careless, whereas both very infrequent and frequent blinkers are rated as “unfriendly” (Omori and Miyata, 2001 ). In addition, political candidates with low blink rates are rated less favorably than those with normal blink frequencies (Patterson et al, 1992 ).…”
Section: Introductionmentioning
confidence: 99%